Easily‐Controlled Chemoselective Hydrogenation by using Palladium on Boron Nitride. Issue 8 (11th June 2013) - Yabe, Yuki; Sawama, Yoshinari; Yamada, Tsuyoshi; Nagata, Saori; Monguchi, Yasunari; Sajiki, Hironao
Abstract The hydrogenation catalyzed heterogeneously by palladium on boron nitride (Pd/BN) in methanol realized the chemoselective hydrogenation of only azides, alkenes, and alkynes in the presence of other reducible functionalities such as benzyl ethers, aryl halides, aryl ketones, and nitro groups. Furthermore, the totally chemoselective semihydrogenation of alkynes could also be achieved without the reduction of other coexisting reducible functionalities, which include azides and alkenes, by using Pd/BN in pyridine as a solvent.